Diversification of Tourism Offer as a Means of Socio-economic Development of Peripheral Regions – Case Study of Kupres - Mirić, Ranko; Drešković, Nusret; Avdić, Boris (Journal for Geography, 2016)
Many modern countries have significant problems with disparities in development between core and periphery. Municipality of Kupres in Bosnia and Herzegovina is one typical example of peripheral area, which is located within the sparsely populated region of Dinaric Karst Highland. It is taken for the case study in this paper, because it shows certain signs of economic activation in the field of tourism. However, its mainstream tourism offer is of seasonal character, and it is not sufficient for sustainable economic growth and significant progress in socio-economic sense. That is why tourism offer need to become more diversified. Methodology in this paper is focused on analysis of all potentials and motives that wider area of Kupres possesses, which can be valorized through systematic approach of institutions and local community. It is intended to emphasize a significance of geographical expertise in these kinds of problematic. Field research and GIS analysis are used for exploration of study area.